Synthesis and Structural Characterization of Transition Metal(II) Complexes with Monobasic Tetradentate (NOOS donor) Ligand - SRIVASTAVA, K.P.; KUMAR OJHA, NIRMAL (Asian Journal of Chemistry, 2010)
The α-mercapto-2-amino phenylacetohydroxamic acid (MAPAH) and its coordination compounds with Co(II), Ni(II) , Cu(II), Zn(II) and Cd(II) ions have been synthesized and characterized on the basis of elemental analyses, magnetic and conductance measurements, IR and electronic spectral studies. The shifts of carbonyl ν(C=O), thloalcohoHc ν(C-S), alcoholic ν(O-H) and amino ν(N-H) stretches in complexes indicated the monobasic tetradentate (NOOS donor) nature of the ligand (MAPA-H). The Co(II) and Ni(II) complexes were paramagnetic and possessed octahedral geometry. The Cu(II) complex was paramagnetic with distorted octahedral geometry. The Zn(II) and Cd(II) complexes were diamagnetic and tetrahedral.